2015
DOI: 10.1039/c5ra05884h
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic extraction of heavy rare earth elements using EHEHP-type and BTMPP-type functional ionic liquids

Abstract: Heavy rare earth elements (HREEs) are more important than light rare earth elements (LREEs) since the supply risk and application in clean energy. In this paper, we first reported the synergistic extraction based on 2-ethyl(hexyl) phosphate mono-2-ethylhexyl ester (EHEHP)-type and bis-(2,4,4-trimethylpentyl) phosphate (BTMPP)-type acid base coupling bifunctional ionic liquids (ABC-BILs) for HREEs separation. Extractabilities of the novel systems were better than those of mixed 2-ethyl(hexyl) phosphonic acid mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The anionic siloxy oxygen was also reported in some other papers. , When the sol–gel polymerization of TEOS proceeded in the organic gel state, the gelator strands acted as a template, which eventually created a void in the resultant silica . In our earlier study, the extraction mechanism of functionalized IL for REE was indicated to be ion association (i.e., the IL’s cation revealed obvious electrostatic interaction with the negative species formed by REE and IL’s anion). , On the basis of the investigations mentioned above, herein the porogen effects of [P 66614 ]­[EHEHP] and [N 1888 ]­[BTMPP] together with the electrostatic interactions between anionic silicate, ILs, and REE are concluded to be as Scheme .…”
Section: Resultsmentioning
confidence: 56%
“…The anionic siloxy oxygen was also reported in some other papers. , When the sol–gel polymerization of TEOS proceeded in the organic gel state, the gelator strands acted as a template, which eventually created a void in the resultant silica . In our earlier study, the extraction mechanism of functionalized IL for REE was indicated to be ion association (i.e., the IL’s cation revealed obvious electrostatic interaction with the negative species formed by REE and IL’s anion). , On the basis of the investigations mentioned above, herein the porogen effects of [P 66614 ]­[EHEHP] and [N 1888 ]­[BTMPP] together with the electrostatic interactions between anionic silicate, ILs, and REE are concluded to be as Scheme .…”
Section: Resultsmentioning
confidence: 56%
“…Several studies have proposed the extraction stoichiometry when ammonium-based ionic liquids were used as extractant in metal extraction processes. In those studies, a solvation mechanism was reported when the ionic liquids were diluted in molecular diluents. ,, However, the equilibrium pH of those works was around a value of 4. In this study, the initial pH was around a value of 0.5 to ensure the extraction of the MoO 2 2+ cation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In those studies, a solvation mechanism was reported when the ionic liquids were diluted in molecular diluents. 32,35,38 However, the equilibrium pH of those works was around a value of 4. In this study, the initial pH was around a value of 0.5 to ensure the extraction of the MoO 2 2+ cation.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the extraction sequence of Ln(III) was also attributed to its ionic radius. This result can be related to the hydration energy of the Ln(III) ion during extraction [ 21 , 28 ].…”
Section: Resultsmentioning
confidence: 99%